Real and potential mercury accumulation in human scalp of adolescents: a case study - Vieira, H. C.
Mercury (Hg) concentration in human hair is used to estimate methylmercury (MeHg) exposure and establish a reference dose for MeHg intake. In this study, Hg accumulation and MeHg intake were evaluated in relation to fish consumption habits in adolescents from two coastal areas: Angra do Heroísmo (Azores archipelago) and Murtosa (Portuguese mainland). Results showed that Hg concentration and MeHg intake increased with increasing fish consumption. In spite of that, Hg concentrations remained relatively low when compared with World Health Organization “no observed adversary effect level”; therefore, risk for mercury exposure should not be considered. Adolescents revealed a similar range of Hg concentrations (0.03–2.60 μg g−1) in scalp hair, apart from being exposed to natural or anthropogenic Hg source (Azores and Mainland, respectively). Nevertheless, Mainland volunteers generally exhibited higher values of Hg accumulation, being approximately 50 % of the results above 1 μg g−1. Hg concentrations increased in both adolescent groups according to the weekly rate of fish meals, however, not linearly in the highest fish consumption rates. In fact, considering the adolescents’ group having over one fish meal per week, the Hg bioaccumulation pattern found in the respective scalp hair suggests the ability of the human body to induce a self-protection response, probably mitigating Hg levels in the blood when experiencing increasing Hg exposure due to fish uptake. Actual and potential mercury levels in human scalp of adolescents probably diverge as fish consumption increases, the effective Hg uptake being lower than the expected, reducing risk to human health.